The Titanic treasure - Luper, Eric (Luper, Eric. Key hunters, 2017)
This time Cleo, Evan, the evil Mr. Locke, and his two trolls have all been transported to the Titanic--and if they do not find and save the priceless jeweled copy of the Rubiyat before the ship hits the iceberg and sinks they may all be lost at sea.